1980
DOI: 10.1002/cber.19801130714
|View full text |Cite
|
Sign up to set email alerts
|

Azomethine, 1‐Azaallyl‐Anionen und metastabile sek. Enamine

Abstract: Die E/Z-Gleichgewichtskonstanten der Keton-anile 6 a -s hangen nicht wesentlich vom induktiven Substituenteneffekt ab. Die fur eine Zuordnung geeigneten ' H-NMR-Verschiebungen gelten auch fur vergleichbare, meist isomerenfreie Azomethine 6 aa-pp und gehorchcn dem Anisotropiemodell. Durch Metallierung entstehen die 1-Azaallyl-Anionen 7; diese werden 'H-NMRspektroskopisch charakterisiert. Kinetische und thcrmodynamische Reaktionslenkung fuhren zu unterschiedlichen Vorzugskonfigurationen dieser Anionen; die Metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 82 publications
1
9
0
Order By: Relevance
“…9 As mentioned before, metalated 1-azaallylic anions have a syn (Z)-C-N stereochemistry preference. This configuration has been described and confirmed by ab initio calculations, [10][11][12][13] NMR studies, [14][15][16][17][18][19][20] X-ray analysis, 21,22 and experimental evidence. [23][24][25][26] The experimental evidence was rationalized via ab initio computational studies.…”
Section: The Syn Effectsupporting
confidence: 65%
“…9 As mentioned before, metalated 1-azaallylic anions have a syn (Z)-C-N stereochemistry preference. This configuration has been described and confirmed by ab initio calculations, [10][11][12][13] NMR studies, [14][15][16][17][18][19][20] X-ray analysis, 21,22 and experimental evidence. [23][24][25][26] The experimental evidence was rationalized via ab initio computational studies.…”
Section: The Syn Effectsupporting
confidence: 65%
“…In contrast, for 8 all three isomers ( 8a − c ) were interconverting. Several dynamic processes have been described for complexes containing 1-azaallyl or 2-pyridylalkyl moieties: (i) for conversion of 1-azaallyl anions (Li, Mg, Al, and Zn 40 ) having the kinetically controlled E -configuration into the thermodynamically stable Z -configuration; and (ii) the fluxional behavior of the tin(II) 2-pyridylalkyls [Sn{η 2 -CR 2 C 5 H 4 N-2} 2 ], [Sn{η 2 -CR 2 C 5 H 4 N-2}Cl], and [Sn{η 2 -CR 2 C 5 H 4 N-2}N(R) 2 ] . As for (ii), the significant variation of δ[ 119 Sn{ 1 H}] with temperature for the three compounds was attributed to a weak dative pyridyl-N−Sn bond.…”
Section: Resultsmentioning
confidence: 99%
“…This has been demonstrated very nicely by Anderson, Casarini, and Lunazzi34 recently who showed that whereas 1-(diethylamino)cyclohexene (9) exists in a conformation with the lone pair "near to orthogonal to the -plane (LPO), and the nitrogen pyramid considerably flattened so that the two nitrogen substituents are near the plane" 2-(die thy lamino) -1 -methylcyclohexene exists in a conformation (10) with the lone pair near the plane (LPP).…”
Section: Introductionmentioning
confidence: 80%